Analysis of the Impact of Urbanization on Household Food Security in Suburban Areas - Asikin, Muhamad Zaenal (Jurnal Multidisiplin Indonesia, 2024)
This study investigates the impact of urbanization on household food security in suburban areas, focusing on the shift from self-sufficient food production to increased reliance on market-based food systems. Using a qualitative research approach, the study collects data from 40 households through in-depth interviews and focuses on the effects of urban sprawl, economic pressures, and changing food consumption patterns. The findings reveal a significant decline in agricultural practices, a reduction in food diversity, and a growing dependence on external food markets. As a result, households face challenges in maintaining nutritional food security, with processed foods becoming more common. Despite these difficulties, households have adopted various coping mechanisms, including income diversification and urban gardening, to mitigate food insecurity. The study also identifies the importance of community support networks in enhancing food resilience. These findings highlight the need for targeted policies that promote sustainable food systems, strengthen food access, and support urban agriculture to improve food security in suburban contexts.